Processing of complex-shaped collimators made via binder jet additive manufacturing of B4C and pressureless melt infiltration of Al. (15th October 2019) - Cramer, Corson L.; Elliott, Amy M.; Kiggans, James O.; Haberl, Bianca; Anderson, David C.
Abstract: Complex collimator geometries are desired for custom neutron scattering applications. Boron carbide (B4 C) is a suitable candidate collimator material because its high boron content results in a large neutron-absorbing cross section and it can be safely processed with powders and subsequent melt infiltrations. High-density collimator geometries of boron carbide-aluminum metal matrix composites were fabricated using binder jet additive manufacturing followed by pressureless melt infiltration with Al alloys. Infiltration of three different Al alloys was demonstrated and the effects of processing time on one alloy were analyzed. During processing, additional reactant phases were produced, and the resulting microstructure was analyzed. Collimator samples produced had high densities and hardness as well as favorable neutron scattering results. Graphical abstract: Unlabelled Image Highlights: B4 C is printed using binder jet additive manufacturing for collimators. Composites of B4C-Al are made by melt infiltration of Al into the B4C preform. Microstructure shows high density and reaction, ternary phase. Mechanical properties show high ductility. Neutron beam tests prove the collimator works well.